IL-22 initiates an IL-18-dependent epithelial response circuit to enforce intestinal host defence - Chiang, Hung-Yu; Lu, Hsueh-Han; Sudhakar, Janaki N.; Chen, Yu-Wen; Shih, Nien-Shin; Weng, Yi-Ting; Shui, Jr-Wen (Nature communications, 2022)
IL-18 is emerging as an IL-22-induced and epithelium-derived cytokine which contributes to host defence against intestinal infection and inflammation. In contrast to its known role in Goblet cells, regulation of barrier function at the molecular level by IL-18 is much less explored. Here we show that IL-18 is a bona fide IL-22-regulated gate keeper for intestinal epithelial barrier. IL-22 promotes crypt immunity both via induction of phospho-Stat3 binding to the Il-18 gene promoter and via Il-18 independent mechanisms. In organoid culture, while IL-22 primarily increases organoid size and inhibits expression of stem cell genes, IL-18 preferentially promotes organoid budding and induces signature genes of Lgr5 + stem cells via Akt-Tcf4 signalling. During adherent-invasive E. coli (AIEC) infection, systemic administration of IL-18 corrects compromised T-cell IFNγ production and restores Lysozyme + Paneth cells in Il-22 −/− mice, but IL-22 administration fails to restore these parameters in Il-18 −/− mice, thereby placing IL-22-Stat3 signalling upstream of the IL-18-mediated barrier defence function. IL-18 in return regulates Stat3-mediated anti-microbial response in Paneth cells, Akt-Tcf4-triggered expansion of Lgr5 + stem cells to facilitate tissue repair, and AIEC clearance by promoting IFNγ + T cells. IL-22 induces IL-18 expression by intestinal epithelial cells. Authors show here that IL-18 is a key barrier maintenance factor during adherent-invasive E. coli invasion, inducing expression of anti-microbial genes in Paneth cells via Stat3, prompting IFNγ expression in T cells and triggering intestinal Lgr5 + stem cell expansion via Tcf4.